2019
DOI: 10.1111/eos.12616
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of metformin on human periodontal ligament stem cells cultured with polydopamine‐templated hydroxyapatite

Abstract: Polydopamine‐templated hydroxyapatite (tHA) is a type of nano‐biomaterial that can promote osteogenesis in bone tissue engineering. However, high concentrations of tHA stimulate production of reactive oxygen species (ROS), resulting in cell injury and apoptosis. Metformin has been demonstrated to activate the adenosine monophosphate‐activated protein kinase (AMPK) signaling pathway, which induces autophagy and decreases ROS production to prevent apoptosis. The present study was performed to investigate the pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 49 publications
0
17
0
Order By: Relevance
“…Further studies have found that HAP-induced autophagy is achieved through the mTOR signaling pathway in a concentration-dependent manner [112] which, in turn, enhances the osteogenic differentiation [112]. Another study verified that polydopamine-templated hydroxyapatite (tHA) resulted in induced cell cytotoxicity and reactive oxygen species (ROS) accumulation by inhibiting the expression of autophagy-related proteins beclin1 and LC3II in human periodontal ligament stem cells (hPDLSCs) [109]. The combination of tHA and metformin may prevent cytotoxicity in hPDLSCs exposed to tHA by reducing ROS via regulations on autophagy-related AMPK/mTOR signaling pathways, an effect that enhances the osteogenic differentiation of hPDLSCs [109].…”
Section: Porous Nano-hydroxyapatite (Nhap)mentioning
confidence: 95%
See 2 more Smart Citations
“…Further studies have found that HAP-induced autophagy is achieved through the mTOR signaling pathway in a concentration-dependent manner [112] which, in turn, enhances the osteogenic differentiation [112]. Another study verified that polydopamine-templated hydroxyapatite (tHA) resulted in induced cell cytotoxicity and reactive oxygen species (ROS) accumulation by inhibiting the expression of autophagy-related proteins beclin1 and LC3II in human periodontal ligament stem cells (hPDLSCs) [109]. The combination of tHA and metformin may prevent cytotoxicity in hPDLSCs exposed to tHA by reducing ROS via regulations on autophagy-related AMPK/mTOR signaling pathways, an effect that enhances the osteogenic differentiation of hPDLSCs [109].…”
Section: Porous Nano-hydroxyapatite (Nhap)mentioning
confidence: 95%
“…Another study verified that polydopamine-templated hydroxyapatite (tHA) resulted in induced cell cytotoxicity and reactive oxygen species (ROS) accumulation by inhibiting the expression of autophagy-related proteins beclin1 and LC3II in human periodontal ligament stem cells (hPDLSCs) [109]. The combination of tHA and metformin may prevent cytotoxicity in hPDLSCs exposed to tHA by reducing ROS via regulations on autophagy-related AMPK/mTOR signaling pathways, an effect that enhances the osteogenic differentiation of hPDLSCs [109]. On the other hand, hierarchically constructed bone-mimetic selenium-doped hydroxyapatite nanoparticles (B-SeHANs) promote the induction of autophagy and apoptosis via the ROS-mediated JNK-activation and AKT/mTOR-inhibition pathways in human MNNG/HOS osteosarcoma cells that suppressed bone tumor growth and reduced bone destruction [110].…”
Section: Porous Nano-hydroxyapatite (Nhap)mentioning
confidence: 96%
See 1 more Smart Citation
“…Dental pulp stem cells activate autophagy as a pro-survival cytoprotective mechanism in response to hydroxyethyl methacrylate injury [ 29 ]. Metformin may prevent cytotoxicity in hPDLCs exposed to Polydopamine-templated hydroxyapatite by reducing ROS via autophagy-related signaling pathways, and may also enhance osteogenic differentiation in hPDLCs [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, high concentrations of tHA stimulated ROS production, resulting in cell injury and apoptosis in PDLSCs. Nevertheless, the triggering of the AMPK/mTOR signaling pathway when tHA is in combination with metformin, led to autophagy activation and consequent increased viability of human PDLSCs with a further improvement of the osteogenic effect [149].…”
Section: Ceramicsmentioning
confidence: 99%